PENINGKATAN KETAHANAN PANGAN PONDOK PESANTREN DARUL MUKHLASIN PALAS, PEKANBARU MELALUI BUDIDAYA TANAMAN: INCREASING OF FOOD SECURITY IN DARUL MUKHLASIN PALAS ISLAMIC BOARDING SCHOOL TOWARD PLANT CULTIVATION - Sri Utami Lestari; Indra Purnama; Seprita Lidar; Fikratul Ihsan; Anna Anggraini (Bersama : Jurnal Pengabdian Kepada Masyarakat, 2023)
The results of an initial survey conducted by the team found that the Darul Mukhlasin Palas Islamic Boarding School in Pekanbaru is for the continuation of the learning process and to meet their daily consumption needs without charging any fees. This Islamic boarding school has a large land of around ±0.5 ha which has the potential to be developed, through increasing food self-sufficiency. The strategy for realizing food self-sufficiency is the development of food diversification. This problem is needed to solve, including: providing partners with training in plant cultivation skills, processing unproductive land into productive land for crop cultivation. The method of implementation includes the provision of materials and the practice of cultivating agricultural crops, mentoring. For the sustainability of this program the PKM team will carry out: Monitoring and Evaluation of program implementation. The results of the training participants' questionnaire above show that the participants' knowledge about plant cultivation has increased, knowledge about the benefits of plant cultivation which may have been considered not so important for human life has increased their knowledge of the benefits of cultivating plants both economically and environmentally. The results of the questionnaire showed that in terms of the benefits of the activities carried out, it was shown that the results of the pre-test questionnaire showed that 100% of participants stated that the activities carried out were useful. In principle, in terms of supporting factors, related parties, both partners and participants, gave a very good response. Capacity building in the technical aspects of agriculture is one of the principles of economic empowerment, including students at Islamic boarding schools.Keywords: food security, boarding school, plant cultivation